The Katalis neurogenesis: ethical perspective - Md Zain, Rosnani; Nik Muhamad Affendi, Nik Rafidah (Human Resource Management Academic Research Society, 2022)
Ethics is a statement about the good and bad of human behavior and becomes one of the essential elements in human life. Therefore, the aspect of ethics needs to be emphasized in human life from childhood so that when they grow up, this ethics is a practice to produce a just, harmonious and prosperous social institution. Recognizing the importance, literary works, especially novels, also raise questions about ethics. To that end, this study will analyze the novel Katalis Neurogenesis by Rosli Mohamad Ali to show the ethics highlighted by the author. Qualitative research, literature, and text analysis are the research methods used in this research. Researchers also use the theory of SEB4K founded by Mohd Yusof Hasan as a platform to discuss ethical issues in literary works. Studies conclude that ethics works to shape a noble personality, a perfect human being, and happy life.